Evaluation of the mucolytic activity of ethanol extract of Temu Ireng (Curcuma aeruginosa Roxb.) - Waznah, Urmatul; Mufrodah, Nely; Wirasti, Wirasti; Mugiyanto, Eko (Universitas Muhammadiyah Malang, 2024)
Curcuma aeruginosa Roxb., known as Temu Ireng, is a species within the Zingiberaceae family that has been empirically noted for its potential as a cough remedy. Temu Ireng contains alkaloids, flavonoids, and saponins, which play crucial roles in mucus liquefaction. This study aims to investigate the mucolytic activity of the ethanol extract of Curcuma aeruginosa Roxb. In this study, we used an experimental method. The extract was obtained via maceration and analyzed in vitro for its ability to reduce the viscosity of bovine intestinal mucus using a digital viscometer. Bovine intestinal mucus was utilized due to its compositional similarity to human mucus. Test sample concentrations of the Temu Ireng extract were 1.0%, 1.5%, and 2.0%, with acetylcysteine serving as the positive control. Mucolytic activity was indicated by a decrease in mucus solution viscosity. The data were analyzed using one-way ANOVA. The results demonstrated a decrease in mucus viscosity for the Temu Ireng extract test solutions, with statistical analysis indicating a significant difference between the negative control and both the positive control and the Temu Ireng extract samples at concentrations of 1.5% and 2.0%, with p-values of 0.032 and 0.030 respectively (p<0.05). The study concludes that the ethanol extract of Curcuma aeruginosa Roxb. exhibits mucolytic activity at concentrations of 1.0%, 1.5%, and 2.0%.